Concept Of Further Development Of National Culture And Tasks Facing The Music Teacher - Nazarov Kholmurod Abdujjaforović (Peerian Journals Publishing, 2024)
This article discusses the concept of further development of national culture, the rights, obligations, and main guarantees of the activities of educators, the principles of fair remuneration, incentives and social protection of their labor, and the tasks of music teachers in improving the effectiveness of education and upbringing
Keywords: Art; talent; music; culture